Philosophy of Science: The Key Thinkers - Brown, James Robert (London Continuum, 2012)
All the great philosophers from Plato and Aristotle to the present day have been philosophers of science. However, this book concentrates on modern philosophy of science, starting in the nineteenth century and offering coverage of all the leading thinkers in the field including Whewell, Mill, Reichenbach, Carnap, Popper, Feyerabend, Putnam, van Fraassen, Bloor, Latour, Hacking, Cartwright and many more. Crucially the book demonstrates how the ideas and arguments of these key thinkers have contributed to our understanding of such central issues as experience and necessity, conventionalism, logical empiricism, induction and falsification, the sociology of science, and realism.
Keywords: 19th Century (1801-1900); 20th Century (1901-2000); Philosophy; Science